2017
DOI: 10.22211/cejem/68443
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Explosion Performance of RDX/AP-based Aluminized Explosives

Abstract: Abstract:To understand the underwater explosion (UNDEX) performance of RDX/AP-based aluminized explosives, six formulations of the explosives were prepared, with Al content varying from 30% to 55% and ammonium perchlorate (AP) content from 45% to 20%. A series of UNDEX tests that used a 1 kg cylindrical charge was conducted underwater at a depth of 4.7 m. The pressure histories of the shock wave produced at different positions and the bubble periods were measured. The coefficients of the similarity law equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Simulation of detonation of Australian‐made PBX‐115 (43/25/20/12 AP/Al/RDX/HTPB) has shown that the detonation velocity and critical diameter are sensitive to the assumed AP decomposition rate . The energy output of RDX/AP‐based aluminized explosives of various formulations can control the fracture process, increment of the energy efficiency, and improvement of the blast effects . The underwater explosion experiments were used to investigate the explosion energy released from hexanitrohexaazaisowurtzitane (CL‐20) and HMX based aluminized explosives .…”
Section: Non‐ideal Behavior Of Chnofcl(al/ap) Explosivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation of detonation of Australian‐made PBX‐115 (43/25/20/12 AP/Al/RDX/HTPB) has shown that the detonation velocity and critical diameter are sensitive to the assumed AP decomposition rate . The energy output of RDX/AP‐based aluminized explosives of various formulations can control the fracture process, increment of the energy efficiency, and improvement of the blast effects . The underwater explosion experiments were used to investigate the explosion energy released from hexanitrohexaazaisowurtzitane (CL‐20) and HMX based aluminized explosives .…”
Section: Non‐ideal Behavior Of Chnofcl(al/ap) Explosivesmentioning
confidence: 99%
“…Distribution forms of energy of explosives reacting underwater can be used to evaluate explosives output performance. Initiation position, manner and Al/O ratio on characteristics of the explosives were studied for underwater detonation . For assessment of the effectiveness of explosives, the knowledge of the peak pressure of the shock wave, attenuation time constant, shock wave impulse, energy, bubble period, and energy flux density is important in the underwater detonation .…”
Section: Non‐ideal Behavior Of Chnofcl(al/ap) Explosivesmentioning
confidence: 99%
“…Since there is a difference of energy construction between the explosion in air and in water, distribution forms of energy of explosives reacting underwater are one of the main indexes evaluating explosives output performance. Initiation position, manner, aluminum‐oxygen ratio compared with TNT, on characteristics of the explosives in the underwater explosion were studied for underwater detonation . Some theoretical researches have been done to calculate the effect of charge construction on energy transmission and comparison with experimental results as well as shock propagation rule underwater , .…”
Section: Introductionmentioning
confidence: 99%
“…Initiation position, manner, aluminum‐oxygen ratio compared with TNT, on characteristics of the explosives in the underwater explosion were studied for underwater detonation . Some theoretical researches have been done to calculate the effect of charge construction on energy transmission and comparison with experimental results as well as shock propagation rule underwater , . Simulation of gas bubble expansion process of PBXW‐15 underwater and the effect of aluminum size (40 mm and 72 mm) on detonation energy have also been studied .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation